Creatine transporter–deficient rat model shows motor dysfunction, cerebellar alterations, and muscle creatine deficiency without muscle atrophy. Issue 2 (26th December 2021) - Duran‐Trio, Lara; Fernandes‐Pires, Gabriella; Grosse, Jocelyn; Soro‐Arnaiz, Ines; Roux‐Petronelli, Clothilde; Binz, Pierre‐Alain; De Bock, Katrien; Cudalbu, Cristina; Sandi, Carmen; Braissant, Olivier
Abstract: Creatine (Cr) is a nitrogenous organic acid and plays roles such as fast phosphate energy buffer to replenish ATP, osmolyte, antioxidant, neuromodulator, and as a compound with anabolic and ergogenic properties in muscle. Cr is taken from the diet or endogenously synthetized by the enzymes arginine:glycine amidinotransferase and guanidinoacetate methyltransferase, and specifically taken up by the transporter SLC6A8. Loss‐of‐function mutations in the genes encoding for the enzymes or the transporter cause creatine deficiency syndromes (CDS). CDS are characterized by brain Cr deficiency, intellectual disability with severe speech delay, behavioral troubles, epilepsy, and motor dysfunction. Among CDS, the X‐linked Cr transporter deficiency (CTD) is the most prevalent with no efficient treatment so far. Different animal models of CTD show reduced brain Cr levels, cognitive deficiencies, and together they cover other traits similar to those of patients. However, motor function was poorly explored in CTD models, and some controversies in the phenotype exist in comparison with CTD patients. Our recently described Slc6a8 Y389C knock‐in rat model of CTD showed mild impaired motor function, morphological alterations in cerebellum, reduced muscular mass, Cr deficiency, and increased guanidinoacetate content in muscle, although no consistent signs of muscle atrophy. Our results indicate that such motor dysfunction co‐occurred with both nervous and muscle dysfunctions, suggesting that muscle strength and performance as well as neuronal connectivity might be affected by this Cr deficiency in muscle and brain.